Intraindividual variability in self-esteem measures: An application of the latent change variable models - Buško, Vesna (Array, 2005)
The developmental changes in general self-esteem were analyzed on a sample of 308 seventh and eight grade primary school participants of both sexes. The data on the general self-esteem were collected in the preadolescent sample on four occasions of measurement within the two year period. Following the assumptions of the latent state-trait theory, the measurement models were defined to represent the degree to which variations in self-esteem measures were due to individual dispositions and/or to occasion-related influences. Further, the models of LST theory were specified to include the latent variables corresponding to the state variability and the trait change in self-esteem scores. By use of the true change modeling procedures it was shown the identified latent change variables were found to be related to the measures of students’ academic achievement as well as their engagements in sports.